2019
DOI: 10.1002/jia2.25235
|View full text |Cite
|
Sign up to set email alerts
|

ART adherence clubs in the Western Cape of South Africa: what does the sustainability framework tell us? A scoping literature review

Abstract: Introduction In 2007, the antiretroviral therapy (ART) adherence club (AC) model was introduced to South Africa to combat some of the health system barriers to ART delivery, such as staff constraints and increasing patient load causing clinic congestion. It aimed to absorb the growing number of stable patients on treatment, ensure quality of care and reduce the workload on healthcare workers. A pilot project of ACs showed improved outcomes for club members with increased retention in care, reduced loss to foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 56 publications
0
34
0
Order By: Relevance
“…Clients and healthcare workers both reported that clubs provide an overall positive experience and a better quality ART service compared with visiting the clinic monthly. Clients and healthcare workers were in agreement on key health systems issues for effective club implementation, which largely reinforced issues highlighted in previous publications , These included: (i) referral of stable clients to the club, (ii) an ideal club size of ≥20 members (the desired upper limit was not reported), (iii) club services led by a counsellor (iv) using churches or community halls as venues (v) effective communication between all parties, and (vi) timely delivery of prepacked medication.…”
Section: Discussionmentioning
confidence: 66%
“…Clients and healthcare workers both reported that clubs provide an overall positive experience and a better quality ART service compared with visiting the clinic monthly. Clients and healthcare workers were in agreement on key health systems issues for effective club implementation, which largely reinforced issues highlighted in previous publications , These included: (i) referral of stable clients to the club, (ii) an ideal club size of ≥20 members (the desired upper limit was not reported), (iii) club services led by a counsellor (iv) using churches or community halls as venues (v) effective communication between all parties, and (vi) timely delivery of prepacked medication.…”
Section: Discussionmentioning
confidence: 66%
“…As the number of people requiring lifelong ART increases, the need for DSD models will grow. ACs are increasingly seen as an alternate method to improve clinical outcomes in burdened healthcare settings, with the flexibility, acceptability and implementation of the programme strongly contributing to its sustainability [47]. Additionally, patients have reported improved satisfaction with the convenience of ACs [28,48].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, innovative strategies such as adherence clubs can help to improve national retention in care for new and long-term HIV patients. Much can be learned from more than 10 years of experience with AC in South Africa [27]. The AC model is being rolled out by the Ministry of Health of Mozambique, and second-line patients from CRAM were transferred to other healthcare centres where new AC have been formed based on our model.…”
Section: Discussionmentioning
confidence: 99%